Critical affect : the politics of method - Barnwell, Ashley (Edinburgh University Press, 2020)
Critical Affect explores the emotional complexity of critique and maps out its enduring value for the turn to affect and ontology. Through a series of vivid close readings, Ashley Barnwell shows how suspicion and methods of decoding remain vital to both civic and academic spaces, where concerns about precarity, transparency, and security are commonplace and the question of how we verify the truth is one of the most polarising of our age.--